Kompetensi program studi Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta - Universitas_Islam_Negeri_Sunan_Kalijaga (Pokja Akademik UIN Sunan Kalijaga, 2006)
isr, c.1-25/stoc4, c.1-15/stoc6, c.16-25